Effect of New Eco-Polyols Based on PLA Waste on the Basic Properties of Rigid Polyurethane and Polyurethane/Polyisocyanurate Foams - Marcin Borowicz (International Journal of Molecular Sciences, 2021)
The aim of the presented research was to obtain two new eco-polyols based on waste polylactide (PLA) and to check the effect on the properties of rigid polyurethane (RPU) foams and, based on these, rigid polyurethane/polyisocyanurate (RPU/PIR) foams. The synthesis of eco-polyols was based on the transesterification reaction of melted PLA with diethylene glycol in the presence of an organometallic catalyst. Properties of the obtained eco-polyols were examined for their potential as raw materials for synthesis of rigid polyurethane and polyisocyanurate foams, i.e., hydroxyl value, acid value, density, viscosity, pH, water content. Spectroscopic studies (FTIR, 1H NMR and 13C NMR) were also carried out. Results of these tests confirmed the assumed chemical structure of the new polyols. RPU and RPU/PIR foam formulations were developed based on the obtained analytical results. Partial replacement of petrochemical polyol by eco-polyols in RPU and RPU/PIR foams decreased the value of apparent density, compressive strength, brittleness and water absorption. Moreover, all foams modified by eco-polyols showed higher resistance to aging. All RPU/PIR foams and most PRU foams modified by eco-polyols from waste PLA had better functional properties than the reference foams based on petrochemical polyol.